A multi-objective method to align human resource allocation with university strategy. (2nd January 2016) - Bouillard, Philippe
Abstract : Universities are currently under considerable pressure to reach their stakeholders' expectations. Management tools that use strategic plans, key performance indicators and quality assurance methods are increasingly deployed. This paper aims to demonstrate how resource allocation can be aligned with institutional strategic plans with a very simple multi-objective optimisation method. The method has been tested and successfully implemented at the Université Libre de Bruxelles. It has been designed for a certain specific context (public university with human resources managed at the institutional level) but could be easily adapted for other contexts.